2018
DOI: 10.1111/fwb.13178
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem structure and function of afrotropical streams with contrasting land use

Abstract: Land use changes can strongly influence stream ecosystems, yet these effects remain poorly documented in many hotspots of deforestation such as tropical Africa. The few studies conducted in this region have mostly focused on structural aspects of stream integrity; sparse data are available for key ecosystem processes such as ecosystem metabolism and litter decomposition. To address this knowledge gap, we measured multiple ecosystem functions in rainforest and nearby agricultural (farm) streams located in an af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 77 publications
(162 reference statements)
1
20
1
Order By: Relevance
“…Our GPP values were similar to other studies in the neighboring Cerrado region (<0.1-0.818 g m −2 d −1 ; [95,96]), the Peruvian Amazon (0.07-0.189 g m −2 d −1 ; [97]), and forested headwater tropical streams more broadly, which typically have very low or undetectable rates of GPP [9,92,93,98,99]. Rates of ER ranged from 0.1-11.9 g m −2 d −1 , which was similar to studies from the Cerrado (0.12-19.58 g m −2 d −1 ; [95,96,99], Amazon (1.8-15. Although we found no land use or seasonal differences in rates of GPP, it was more frequently measurable and, thus, higher in cropland streams than forested streams (Tables S7 and S8, Figure 5), similar to studies showing greater GPP in agricultural streams [92,100,101]. We measured lower rates of GPP than reported in streams where riparian forest cover was highly disturbed or absent, e.g., [92,93].…”
Section: Stream Metabolismsupporting
confidence: 82%
See 1 more Smart Citation
“…Our GPP values were similar to other studies in the neighboring Cerrado region (<0.1-0.818 g m −2 d −1 ; [95,96]), the Peruvian Amazon (0.07-0.189 g m −2 d −1 ; [97]), and forested headwater tropical streams more broadly, which typically have very low or undetectable rates of GPP [9,92,93,98,99]. Rates of ER ranged from 0.1-11.9 g m −2 d −1 , which was similar to studies from the Cerrado (0.12-19.58 g m −2 d −1 ; [95,96,99], Amazon (1.8-15. Although we found no land use or seasonal differences in rates of GPP, it was more frequently measurable and, thus, higher in cropland streams than forested streams (Tables S7 and S8, Figure 5), similar to studies showing greater GPP in agricultural streams [92,100,101]. We measured lower rates of GPP than reported in streams where riparian forest cover was highly disturbed or absent, e.g., [92,93].…”
Section: Stream Metabolismsupporting
confidence: 82%
“…We found no significant effect of land use on ER. Other studies in tropical headwater streams have generally found ER to be higher in agricultural watersheds than forested watersheds [92,93,[95][96][97] but not always [99,100]. The major difference we observed was that ER did not change seasonally in forested streams but was~2.8 times greater in the wet season compared to the dry season in cropland streams.…”
Section: Stream Metabolismcontrasting
confidence: 70%
“…Although data is limited, the status of African freshwater resources is one of a general decline (Darwall et al, 2011;UNEP-WCMC, 2016). Major concerns have been raised on the effects of pollution, urbanization, landuse change, overexploitation of biological resources, agriculture and invasive species on water quality and quantity, aquatic biodiversity, nutrient cycling, and energy sources supporting food webs (e.g., Masese et al, 2017;Fugère et al, 2018;Sayer et al, 2018;Matomela et al, 2021). These impacts are reducing ecosystem services offered by rivers and their floodplains, and undermining human well-being across the continent (IPBES, 2018).…”
Section: Ecological Status Of African Riversmentioning
confidence: 99%
“…This approach has been extended to leaf litter decomposition rates (Gessner and Chauvet, 2002;Young and Matthaei, 2008). Several studies have investigated the influence of agriculture on the composition of macroinvertebrates functional feeding groups and leaf litter decomposition in tropical streams (Jinggut et al, 2012;Boyero et al, 2015;Fugère et al, 2018;Cornejo et al, 2020). Compared to temperate streams, higher mean water temperature and low diversity of shredders in tropical streams have been suggested as the main reasons why litter decomposition may be driven mainly by microorganisms (Irons et al, 1994;Boyero et al, 2011;Tiegs et al, 2019).…”
Section: Introductionmentioning
confidence: 99%